2018
DOI: 10.1016/j.applanim.2017.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Is evolution of domestication driven by tameness? A selective review with focus on chickens

Abstract: Domestication of animals offers unique possibilities to study evolutionary changes caused by similar selection pressures across a range of species. Animals from separate genera tend to develop a suite of phenotypic alterations referred to as "the domesticated phenotype". This involves changes in appearance, including loss of pigmentation, and alterations in body size and proportions. Furthermore, effects on reproduction and behaviour are typical. It is hypothesized that this recurring phenotype may be secondar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 41 publications
(53 reference statements)
2
32
0
2
Order By: Relevance
“…For example, in chickens, selecting for tameness over only eight generations have led to the low-fear line having larger growth and body size, laying larger eggs, having a modified metabolism and increased feed efficiency, and displaying a reduced brain size and a modified social behavior. Changes were also observed in gene expression and DNA methylation in the brain (Agnvall et al, 2017).…”
Section: Introduction Domesticationmentioning
confidence: 84%
See 1 more Smart Citation
“…For example, in chickens, selecting for tameness over only eight generations have led to the low-fear line having larger growth and body size, laying larger eggs, having a modified metabolism and increased feed efficiency, and displaying a reduced brain size and a modified social behavior. Changes were also observed in gene expression and DNA methylation in the brain (Agnvall et al, 2017).…”
Section: Introduction Domesticationmentioning
confidence: 84%
“…Selection experiments in modern times, on foxes (Gulevich et al, 2004), rats (Albert et al, 2008) and chickens (Agnvall et al, 2017), have confirmed that selecting only for tameness can in fact lead to the emergence of several of the traits included in the domestic phenotype. For example, in chickens, selecting for tameness over only eight generations have led to the low-fear line having larger growth and body size, laying larger eggs, having a modified metabolism and increased feed efficiency, and displaying a reduced brain size and a modified social behavior.…”
Section: Introduction Domesticationmentioning
confidence: 99%
“…Variation in the timing of egg tooth development and different developmental rates could be related to the level of activity (or degree of precociousness) between red junglefowl and chickens, but to establish this relationship more samples and statistical tests will be needed. Red junglefowls, in comparison with their domesticated counterparts, are more active and show higher fear response . Possibly, this behavioral difference related to the domestication process is coupled with morphological variation and early hatching.…”
Section: Discussionmentioning
confidence: 99%
“…Red junglefowls, in comparison with their domesticated counterparts, are more active and show higher fear response. 96 Possibly, this behavioral difference related to the domestication process is coupled with morphological variation and early hatching.…”
Section: Developmentmentioning
confidence: 99%
“…Increased tolerance towards humans is most often demonstrated by reduced flight initiation distance when approached by a human observer (FID, a widely accepted proxy for risk-taking), a pattern consistent among a high number of species (Blumstein 2019). Disturbance tolerance has a genetic basis, as indicated by selection experiments that successfully produced tolerant lines (Agnvall et al 2018) and by the heritability of FID in wild populations (Bize et al 2012;Møller 2014;Carrete et al 2016). Furthermore, disturbance tolerance appears to be linked to candidate genes (e.g.…”
Section: Human Disturbancementioning
confidence: 99%